Principles of Entrepreneurship (ENT530): Business Model Canvas: Sanivapor Tech / Mazsara Mazlan … [et al.] - Mazlan, Mazsara; Abdul Jalil, Nabila Natasya; Sahaimi, Nur Syakirah; Kamarul Hatta, Nurul Kamilah; Zainal Abidin, Siti Hawa (2021)
SaniVapor Tech is a company that sells mask sterilizer box in Malaysia. This company was established in 2021. We get this idea because we saw that many people nowadays threw their disposable face mask everywhere and it cost them to keep on buying face mask. We create this product because we want to help them to solve their problem. There is currently no other company in Malaysia right now that produces this mask steriliser box with the Vaporized Hydrogen Peroxide (VHP). We usually saw a steriliser box with Ultraviolet (UV) light. Our company is the first one to create this product with that method. Our product is very suitable for those who concern about their hygiene. Because we know that when some people take off their face masks, they will place them anywhere without knowing what bacteria might be on the surface. Therefore, our target market for this product is middle to upper-class income level. When we create this product, our goal is to help people cut their costs by frequently buying face masks. And we also wanted to decrease the environmental problem that causes by people throwing their used face masks. SaniVapor Tech's Business Model Canvas (BMC) will have nine divisions, each with its unique function in its operations, and we will explain it in more detail in this report. We will also provide the Strength, Weakness, Opportunity, and Threat (SWOT) of our company in this report because we want to know what ability to give to consumers out there and what things we need to improve in the future. We also did a comparison on the strength and weakness with two other competitor that produces sterilisers, such as Philips and 59S. We also hope that our company can expand our target audience in the future not only for middle to upper-class income level but also for everyone out there. We also wanted to extend our marketing not only in Malaysia but all over the world. We hope that people can start to recognize the existence of our product in the market.